2020
DOI: 10.1111/jrh.12508
|View full text |Cite
|
Sign up to set email alerts
|

PCP Opinions of Universal Suicide Risk Screening in Rural Primary Care: Current Challenges and Strategies for Successful Implementation

Abstract: Universal suicide risk screening has the potential to address the disproportionately high rates of suicide in the rural United States, as 83% of people who have died by suicide have visited a health care provider in the year prior to their deaths, and rural patients are more likely to visit medical professionals than behavioral health professionals for mental health concerns. This study describes the opinions of primary care providers (PCPs) practicing in a primarily rural state regarding universal suicide ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 68 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…This is the first study to date to investigate HCPs' opinions on depression, SI, ISI, and suicide specifically in diabetes clinics and barriers to care. Previous studies that note mental healthcare concerns in primary care 21,22 are echoed here by diabetes HCPs, including difficulty referring to mental health providers, lack of access, and lack of confidence in asking about mental health concerns. Similar to primary care studies, the majority of diabetes HCPs found that it is important to ask about depression and suicide and want to have more training on how to ask appropriate questions, how to quickly assess risk in clinic, and what to do after an individual reports depression or SI.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This is the first study to date to investigate HCPs' opinions on depression, SI, ISI, and suicide specifically in diabetes clinics and barriers to care. Previous studies that note mental healthcare concerns in primary care 21,22 are echoed here by diabetes HCPs, including difficulty referring to mental health providers, lack of access, and lack of confidence in asking about mental health concerns. Similar to primary care studies, the majority of diabetes HCPs found that it is important to ask about depression and suicide and want to have more training on how to ask appropriate questions, how to quickly assess risk in clinic, and what to do after an individual reports depression or SI.…”
Section: Discussionmentioning
confidence: 92%
“…Primary care studies have evaluated HCPs’ opinions of mental healthcare and specifically suicide risk screening. 21,22 These studies found that HCPs felt screening was important but were concerned about poor access to mental healthcare, disruption to clinical flow when someone screened positive, and overall concern that patients would not attend when a referral was placed. Within diabetes care, studies have shown that in those with positive mental health screening who are referred to mental healthcare, approximately 50% attend a mental healthcare appointment.…”
Section: Introductionmentioning
confidence: 99%
“…Almost half of participants reported being “neutral” or disagreeing with the statement that they felt comfortable completing a risk assessment or a safety plan with a suicidal individual, indicating that this might be an additional area that needs more attention in future trainings. Covering content related to discomfort with the topic of suicide may be beneficial as well, as many primary care providers have reported discomfort to be a main barrier to suicide risk screening and assessment in primary care (LeCloux, Aguinaldo, Lanzillo, & Horowitz, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Studies on suicide risk screening in other clinical settings (eg, emergency departments) suggest there are additional barriers for assessing suicide risk, such as care coordination challenges, and clinician and patient hesitancy to discuss mental health concerns. 21,[27][28][29][30][31] Therefore, studies are needed to identify barriers and facilitators of suicide risk screening programs in cancer care delivery.…”
Section: Original Contributionsmentioning
confidence: 99%